Progress of High‐Throughput and Low‐Cost Flexible Perovskite Solar Cells. Issue 8 (9th February 2020) - Mujahid, Muhammad; Chen, Chen; Hu, Wei; Wang, Zhao-Kui; Duan, Yu
Abstract : In recent years, the era of perovskites has experienced splendid development. Among perovskites, flexible perovskite solar cells (FPSCs) have received increasing attention due to their high efficiency, light weight, low cost, excellent flexibility, and low‐temperature solution processing ability. In the last decade, the power conversion efficiency of FPSCs has increased significantly from 2.62% to more than 20%. Herein, a succinct overview of the current endeavor to achieve low‐temperature FPSCs is provided. The recent developments, including flexible substrates, transparent conductive electrodes, perovskite absorbers, and device manufacturing methods, are vividly discussed. The strategies for enhancing the stability and flexibility of FPSCs are presented in terms of electrode materials, device encapsulation, and structural effects. Finally, the most encouraging and potential studies for the future of flexible PSCs are revealed. Abstract : Flexible perovskite solar cells have attracted plenty of attention in both educational and business communities. Herein, the research background is summarized and technological advancement with regard to flexible substrates is evaluated. In addition, different stability tests with and without encapsulation are briefly examined. Last but not least, the upscaling issues and the material costs are also vividly discussed.